Verbum verbo reddere versus sensum sensui reddere, czyli leksykalna dyferencjacja znaczeń kontekstowych greckiego πάσχα we współczesnych translacjach nowotestamentowych (na tle polskiej tradycji przekładowej) - Lisowski, Tomasz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The analysis aims to indicate the methods of translating the cultureme expressed by the Greek lexeme πάσχα in selected contemporary New Testament renderings. The translators of the Catholic Biblia tyniecka (1971) used formal equivalence that is close to the verbum verbo reddere technique established thanks to the Bible edited by Jakub Wujek (1599). This translation technique also dominates in two later renderings of the Catholic circle, i.e. Biblia poznańska (1975) and Nowy Testament by Kazimierz Romaniuk (1975). However, the translators of the Evangelical Biblia warszawska (1975) as well as the translators of the Evangelical dynamic New Testament (1991) and the ecumenical rendering of the New Testament (2001) distinguished the contextual meanings of the Greek πάσχα, thus realizing the essence of the formula sensum sensui reddere, i.e. of dynamic equivalence. This technique was first used by Daniel Mikołajewski in the Gdańsk Bible (1632). The translators of the latest Catholic Biblia paulińska (2011) refer to this technique as well. This fact unquestionably supports the claim that the tendency to lexically differentiate the meanings of the Greek πάσχα in contemporary Polish renderings, the aim of which is to make the meaning of the biblical message accessible to contemporary recipients, is primarily of a philological rather than religious nature.